How ASEAN can contribute to international AI governance frameworks - Sagun-Trajano, Karryl Kim (2023)
As artificial intelligence is crucial to ASEAN’s goal of becoming a digital economy and society, learning from the practices of other countries and participating in international efforts to establish governance frameworks may help the region plan better for its upcoming ASEAN Guide on AI Governance and Ethics set to be released in 2024.